SAMPAH SEBAGAI SARANA PENINGKATAN EKONOMI KREATIF DAN PELESTARIAN LINGKUNGAN HIDUP DI KOTA MATARAM - Anggreni, Ni Luh Eka Yuli (Guna Sewaka, 2022)
Garbage is an important problem in society and is one of the main causes of environmental pollution. The relationship between human behavior and the natural environment is a reciprocal relationship and provides mutual guarantees for the realization of nature conservation and the concept of sustainability and justice built by the community. Where the environment can affect humans and vice versa human behavior can affect the environment. The purpose of this study is to describe and analyze the community's efforts and constraints in managing waste as a means of improving the creative economy and preserving the environment in the city of Mataram. This study used qualitative research methods. The problems studied used two theories, namely the theory of motivation and the theory of human ecology. The results of this study are as follows: Community efforts to manage waste as a means of improving the creative economy and the environment in the city of Mataram, including, 1) Establish a waste management called Rumpil Inges, Rumpil Inges is an acronym for House of Sorting and Waste Processing, 2) active in intensifying socialization and educating at Rumpil Inges about the importance of sorting out waste from the house, 3) implementing Gotong Royong activities once a week, this activity is also an effort to maintain and improve a healthy environment. The community's obstacles in processing waste as a means of improving the creative economy and environmental preservation in Mataram City are, 1) household waste is not segregated, 2) the level of mindset and awareness of the community is still underdeveloped towards the waste problem, 3). The generation of waste is getting bigger due to the increasing consumptive and growing population (natural/urbanization)